1 mũ 25 : 11 mũ 23 – 3 mũ 5 : (1 mũ 10 + 2 mũ 3) – 60

Photo of author

By Quinn

1 mũ 25 : 11 mũ 23 – 3 mũ 5 : (1 mũ 10 + 2 mũ 3) – 60

0 bình luận về “1 mũ 25 : 11 mũ 23 – 3 mũ 5 : (1 mũ 10 + 2 mũ 3) – 60”

  1. Đáp án:

    `1^{25}:11^{23}-3^5:(1^{10}+2^3)-60`

    $=1:11^{23}-3^5:(1+8)-60$

    $=\dfrac{1}{11^{23}}-3^5:9-60$

    $=\dfrac{1}{11^{23}}-3^5:3^2-60$

    $=\dfrac{1}{11^{23}}-3^{5-2}-60$

    $=\dfrac{1}{11^{23}}-3^{3}-60$

    $=\dfrac{1}{11^{23}}-27-60$

    $=\dfrac{1}{11^{23}}-(27+60)$

    $=\dfrac{1}{11^{23}}-87$

    Giải thích các bước giải:

     

Viết một bình luận